2008
DOI: 10.1590/s0104-530x2008000200015
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos de complexidade do trabalho de coletores de lixo domiciliar: a gestão da variabilidade do trabalho na rua

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 2 publications
0
9
0
14
Order By: Relevance
“…Moreover, as reported by Vasconcelos et al [17], the work of a garbage collector requires constant attention, because the individual must make decisions all the time, whether regarding his safety or the team safety; concerning handling of garbage. These factors may contribute to psychosocial distress at work and consequently to the worsening of musculoskeletal symptoms [8,13].…”
Section: On the Use Of The Body And Some Effects On Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as reported by Vasconcelos et al [17], the work of a garbage collector requires constant attention, because the individual must make decisions all the time, whether regarding his safety or the team safety; concerning handling of garbage. These factors may contribute to psychosocial distress at work and consequently to the worsening of musculoskeletal symptoms [8,13].…”
Section: On the Use Of The Body And Some Effects On Healthmentioning
confidence: 99%
“…As discussed by Santos et al [16] and Vasconcelos et al [17], when a collector is denied a fixed itinerary, his appropriation of work is rendered unviable, for it is prevented the accumulation of experience based on knowledge of local geography and in affective ties established within the team and with the community, which are important factors in the structure of workgroups. This impaires his ability of managing usual and unforeseen events, besides the conflicting goals of quality, time, safety and sparing the body, being subjected to increased workload and to situations of risk and psychological wear.…”
Section: If You Have a Lot Of Garbage You Can't Use One Without Brakmentioning
confidence: 99%
“…Hence Le Boterf (2000) states that to be competent means to have the capacity to act and react in different contexts , to request and combine the necessary and relevant resources to accomplish the task, to understand it and to succeed in its execution. The greater the capacities of the operator, the greater the possibility of dealing with the uncertainties present in the activity (Vasconcelos et al, 2008). In examining the harvester machine operation, it was observed that operators handle several variables (many unpredictable) and risky situations.…”
Section: Competence -Device Relationshipmentioning
confidence: 99%
“…O ponto de vista fisicalista (SMITH, 1999) de avaliação do trabalho não compreende essa duração da vida psíquica nem sua materialização (BERGSON, 1999). Isso resulta em graves riscos para os trabalhadores (acidentes, adoecimentos), que, dotados de expertise, podem ter a sua atividade classificada como simples ou como descartável, ao passo que ela é, de fato, ontologicamente complexa (VASCONCELOS et al, 2008), sob a égide da noção de complexidade na filosofia contemporânea (MORIN, , 1990(MORIN, , 1982.…”
Section: Problema De Pesquisa Teórico-filosóficaunclassified